The archaeological sites in the city of Granada and their role in historical knowledge (635-897 AH / 1237-1492 AD) - Dr. Mohammed Oweid Ghlaim (Journal of College of Education, 2025)
The historical and cultural landmarks of Granada are remarkably diverse, as evidenced by the abundance of its architectural structures, including schools, mosques, churches, palaces, hotels, markets, streets, squares, gates, towers, and baths. Numerous sultans, princes, and rulers in Granada were responsible for constructing these monuments, each for different purposes: to immortalize their legacy, to demonstrate the power and grandeur of their rule, to serve their own personal interests and provide entertainment, and also to meet the needs and daily requirements of the general public, as seen in the construction of public facilities such as markets, hotels, and baths. These monuments exemplify the architectural and engineering advancements of Al-Andalus, reflecting sophisticated design, intricate ornamentation, and high-quality construction, as evidenced by the fact that some of them still stand proudly today. This is further elaborated upon in the main text of the research.